2017
DOI: 10.9740/mhc.2017.07.160
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-emergent hypomania possibly associated with over-the-counter supplements

Abstract: The use of complementary and alternative medicine (CAM) is gaining popularity in the Western world. Among the general public, CAM is often perceived to be associated with less stigma, fewer adverse effects, and may be more affordable. A number of patients utilize CAM for the treatment of depression; however, as there is limited scientific evidence, the safety profile of these supplements are largely unknown. In this case, a 42-year-old man developed hypomania approximately 1 week after S-adenosylmethionine (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…reported that G. simplicifolia and 5‐HTP were sold online as ingredients of ‘designer drugs’ or ‘party pills’ as an alternative to the synthetic psychoactive substance ecstasy [104] . A previous study demonstrated the occurrence of hypomania in a man using 5‐HTP and adenosylmethionine [105] . Another study reported a case of hospitalization due to serotonin syndrome associated with G. simplicifolia /5‐HTP supplementation [106]…”
Section: Ingredients Permitted (Or Not Specified) By Wadamentioning
confidence: 99%
“…reported that G. simplicifolia and 5‐HTP were sold online as ingredients of ‘designer drugs’ or ‘party pills’ as an alternative to the synthetic psychoactive substance ecstasy [104] . A previous study demonstrated the occurrence of hypomania in a man using 5‐HTP and adenosylmethionine [105] . Another study reported a case of hospitalization due to serotonin syndrome associated with G. simplicifolia /5‐HTP supplementation [106]…”
Section: Ingredients Permitted (Or Not Specified) By Wadamentioning
confidence: 99%